KERAJINAN RENDO BANGKU DI NAGARI KOTOGADANG KABUPATEN AGAM PROVINSI SUMATERA BARAT - Putri, Fanny Eka; Ernawati, Ernawati; Novrita, Sri Zulfia (Journal of Home Economics and Tourism, 2015)
The bench is one of the lace crafts products owned by the local communityKotogadangAgam regency of West Sumatra. The purpose of this study was todescribe decorative lace bench based motif, colors and materials, equipment andmanufacturing processes as well as products of craft lace bench at AmaiSetiaFoundation Kotogadang. The technique of collecting data through interviews,observation and documentation. Data analysis technique is data reduction datapresentation and conclusion.The study states that the decorative lace bench mosthave a motive Flora, fauna and motifs inspired by the shape of the object. Coloryarn products depending on the material used. The equipment used is very simple.The process of making is the start of a set peralatanhingga motifs and interestingtwist yarns. Lace handicraft products Bench consisting of household linen, laceends and edges of shawls, wedding dress fittings, and other product